The Mothers of East Los Angeles: (Other)Mothering for Environmental Justice. Issue 5 (20th October 2018) - Thomas, Christopher Scott
ABSTRACT: This essay explores the Mothers of East Los Angeles (MELA)—an environmental justice group started and led by older Mexican American women—and the organization's campaign to prevent the construction of a state prison in their neighborhood. The women enact motherwork that protects the well-being of the neighborhood's children, in addition to crafting motherhood into a communal responsibility to look after the neighborhood as a mother would their child. MELA's maternal appeals rely on and eclipse identification with traditional gender categories, suggesting new ways for motherhood to function as an organizing principle to mobilize collectives. More broadly, this essay contributes to scholarly discussions on rhetorical agency by considering motherhood as a means for women's collective resistance and empowerment.